Development of a biofunctional conductive neural scaffold based on chitosan, polycaprolactone, carvacrol and polyaniline - Ozalp, Elif; Oktay, Busra; Ciftci, Fatih; Erarslan, Azime; Ahlatcioglu Ozerol, Esma (TAYLOR & FRANCIS LTD, 2026)
Damage in neural tissues poses a significant challenge in regenerative medicine, requiring scaffolds that support both biological and electrical functions. Conductive biomaterials offer promising solutions by promoting neural repair and integration. However, the development of multifunctional scaffolds that simultaneously provide electrical conductivity, antioxidant activity, mechanical strength, and biocompatibility remains limited. This study aims to develop and characterize a biofunctional conductive neural tissue scaffold. The incorporation of polyaniline (PANI) enhanced electrical conductivity, while the addition of carvacrol (CRV) improved antioxidant activity and biological function but slightly reduced conductivity in the layered structure. In the second-layer scaffold model, cell viability reached 140% thanks to carvacrol. The electrical conductivity of the chitosan/polyaniline film was measured as 1.429 x10-2 S/m using the four-point probe method. A second layer of polycaprolactone/carvacrol was formed onto the chitosan/polyaniline conductive film using electrospinning, and the conductivity was measured as 1.052 x10-3 S/m. The values obtained for both conductive scaffolds have been shown to provide good electrical conductivity in conductive tissue scaffolds used in neural tissue engineering studies. Polycaprolactone (PCL) contributed to mechanical strength, and chitosan (CHI) improved biocompatibility. The combination of these components resulted in a scaffold with suitable properties for neural tissue repair, particularly under neurodegenerative conditions.
Keywords: Carvacrol; chitosan; neural tissue engineering; polyaniline; polycaprolactone; ESSENTIAL OIL; BIOMATERIALS; FABRICATION; COMPOSITES; GRAPHENE; Materials Science; Polymer Science